Practical Recommendations for Long-term Management of Modifiable Risks in Kidney and Liver Transplant Recipients: A Guidance Report and Clinical Checklist by the Consensus on Managing Modifiable Risk in Transplantation (COMMIT) Group - Neuberger, James M; Bechstein, Wolf O; Kuypers, Dirk R J; Burra, Patrizia; Citterio, Franco; De Geest, Sabina; Duvoux, Christophe; Jardine, Alan G; Kamar, Nassim; Krämer, Bernhard K; Metselaar, Herold J; Nevens, Frederik; et al. (Transplantation, 2017)
Short-term patient and graft outcomes continue to improve after kidney and liver transplantation, with 1-year survival rates over 80%; however, improving longer-term outcomes remains a challenge. Improving the function of grafts and health of recipients would not only enhance quality and length of life, but would also reduce the need for retransplantation, and thus increase the number of organs available for transplant. The clinical transplant community needs to identify and manage those patient modifiable factors, to decrease the risk of graft failure, and improve longer-term outcomes.COMMIT was formed in 2015 and is composed of 20 leading kidney and liver transplant specialists from 9 countries across Europe. The group's remit is to provide expert guidance for the long-term management of kidney and liver transplant patients, with the aim of improving outcomes by minimizing modifiable risks associated with poor graft and patient survival posttransplant.The objective of this supplement is to provide specific, practical recommendations, through the discussion of current evidence and best practice, for the management of modifiable risks in those kidney and liver transplant patients who have survived the first postoperative year. In addition, the provision of a checklist increases the clinical utility and accessibility of these recommendations, by offering a systematic and efficient way to implement screening and monitoring of modifiable risks in the clinical setting.
Keywords: oportunní infekce; Medication Adherence; Humans; Graft Rejection; rizikové faktory; přežívání štěpu; lidé; Checklist; následná péče; imunosupresiva; Liver Transplantation; transplantace jater; Immunosuppressive Agents; Postoperative Complications; transplantace ledvin; pooperační komplikace; Opportunistic Infections; Aftercare; Kidney Transplantation; Risk Assessment; Graft Survival; hodnocení rizik; adherence k farmakoterapii; kontrolní seznam; rejekce štěpu; Risk Factors